Sublingual Dermoid Cyst: Review of 14 Cases - Oluleke, Omisakin Olatunde (Ann Maxillofac Surg, 2020)
BACKGROUND: Dermoid cyst is a benign congenital lesion of ectodermal origin. They are commonly found throughout the body but rare in the oral cavity. It is a developmental lesion and usually due to retention of germinal epithelium during growth of brachial arches and lower jaw. It is commonly present in the sublingual region as a swelling in the middle of the mouth. It presents as a slow growing mass, causing elevation of the tongue and interference with speech and swallowing. AIM AND OBJECTIVE: To determine the epidemiology, presentation, co-morbidities and treatment of sublingual dermoid cyst in our Centre. MATERIALS AND METHODS: This is a retrospective review of all patients with sublingual dermoid cyst managed over a period of eight years from January 2010 to December 2017. Information was extracted from case files of patients. Data collected included: age of patient at presentation, sex, location of cyst, co-morbidities, treatment giving, findings and histological diagnosis. Only patients with a histological diagnosis of dermoid cyst were included in the study. RESULTS: Fourteen cases were included in this study. Eight were males (57.1%) and six (42.9%) females. Male to female ratio is 1.3:1. Age range is from Day 1 to 25years. Five were congenital sublingual dermoid cyst in newborn, one was attached to the tongue ventral surface, two were bulging from the submandibular and submental spaces in adults. The remaining six cases were limited to the floor of the mouth. CONCLUSION: Sublingual dermoid cyst could interfere with swallowing and speech, this affects patient nutrition and breathing. Therefore, surgical excision of the cyst should be done promptly.